IFN‐γ mediates early B‐cell loss in experimental African trypanosomosis. (September 2015) - Cnops, J.; De Trez, C.; Bulte, D.; Radwanska, M.; Ryffel, B.; Magez, S.
Summary African trypanosomes infect humans and animals throughout the African continent. These parasites maintain chronic infections by various immune evasion strategies. While antigenic variation of their surface coat is the most studied strategy linked to evading the host humoral response, African trypanosomes also induce impaired B‐cell lymphopoiesis, the destruction of the splenic B‐cell compartment and abrogation of protective memory responses. Here we investigate the mechanism of follicular B‐cell destruction. We show that during infection follicular B cells undergo apoptosis, correlating to enhanced Fas death receptor surface expression. Investigation of various type 1 cytokine knockout mice indicates a crucial role of IFN‐γ in the early onset of FoB cell destruction. Indeed, both IFN‐γ−/− and IFN‐γR−/− mice are protected from trypanosomosis‐associated FoB cell depletion, exhibiting an inhibition of B‐cell apoptosis as well as a reduced activation of FoB cells during the first week post‐infection. The data presented herein offer new insights into B‐cell dysfunctioning during experimental African trypanosome infections.